2001
DOI: 10.1007/s003300100827
|View full text |Cite
|
Sign up to set email alerts
|

Forearm soft tissue mass caused by an accessory muscle

Abstract: We present a case of forearm soft tissue mass caused by an accessory muscle, distal and deep to flexor carpi ulnaris muscle. Imaging studies, mainly magnetic resonance and ultrasound, allow a specific diagnosis, and obviate unnecessary surgery. In this case, the symptoms associated with ulnar compression led to surgery and confirmed the preoperative diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 6 publications
2
7
0
Order By: Relevance
“…With regards to the imaging literature, there are several MRI illustrations of the accessory FCU in papers by Lemon et al 10 and Milena at al. 5 Milena et al 5 demonstrated a similar accessory muscle on ultrasound and MRI which also had an insertion to pisiform, as in our case. However, the accessory muscle in their case originated more proximally at the lateral edge of the elbow, blending with the ulnar attachment of pronator quadratus.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…With regards to the imaging literature, there are several MRI illustrations of the accessory FCU in papers by Lemon et al 10 and Milena at al. 5 Milena et al 5 demonstrated a similar accessory muscle on ultrasound and MRI which also had an insertion to pisiform, as in our case. However, the accessory muscle in their case originated more proximally at the lateral edge of the elbow, blending with the ulnar attachment of pronator quadratus.…”
Section: Discussionsupporting
confidence: 78%
“…Given the position and location of the accessory muscle, there is potential for ulnar nerve entrapment syndrome with several reports of accessory FCU causing ulnar nerve symptoms that responded well to neurolysis and re-attachment of the distal tendon. 5,8 In the current case, there were no clinical symptoms of ulnar nerve entrapment. When considering ulnar nerve entrapment syndromes of the upper limb, it should be noted that the accessory anconeus epitrochlearis muscle can cause more proximal ulnar nerve compression in the cubital tunnel, having its origin at the medial epicondyle with insertion to the olecranon.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…The ulnar slip of the tendon was inserted into the pisiform bone and the radial slip into the proximal phalanx of the ring finger. Lopez Milena et al (2001) have observed an anomalous DISCUSSION Not many variations of FCU are reported in the literature. Grechenig et al (2000) have conducted an Fig.…”
Section: Case Reportmentioning
confidence: 92%